Pemasaran ikan dan peningkatan taraf hidup nelayan - Ali, Jamal; Viswanathan, K. Kuperan; Kamarudin, Roslina; Halim, Nurul Faizah (Universiti Utara Malaysia, 2012)
Productivity and marketing channel are factors that can influence fishermen income.The objective of the study is to examine factors that will affect the fishermen income in Tuba Island, Langkawi.Incomes of fishermen are determined by type of fishing gears, boat size, demographic factors, type of fish that the fishermen catch, and the way the fishermen market their fish.Questionnaire was distributed to 201 fishermen households in Tuba Island, an island which is undergoing rapid development.The results indicated that landing areas, type of fishing gears and type of fish has significant effect to the fishermen income.It also showed that government support activities, such as the landing jetty have an impact on marketing of fish caught by these fishermen.The finding suggests that improving the marketing channel and improving the fishery resources should be emphasized by policy makers.